Symbiodinium in coral reefs and its adaptation responses toward coral bleaching events : a review - Nurul Shafiqa-Yusof; Nur Syahirah Mohd Radzi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Symbiodinium is a category of symbiotic dinoflagellates commonly associated with various reef-building corals. Detrimental impacts of global climate change worsen the mutualistic association of coral-Symbiodinium, endangering the reefs to the bleaching and mass mortality phenomenon. Destruction of coral reef ecosystems has adverse effects not only on marine life but also on the human population. It has been proposed that to protect the coral reefs, an exclusive selection of thermal-tolerance traits in Symbiodinium will increase the survivability of coral reefs. However, there are still limited findings on the coral-endosymbiont resistance under adverse environments. Thus, this review aims to introduce shortly the coral reefs, Symbiodinium, and coral bleaching events, as well as to provide brief reviews of cellular and molecular responses in Symbiodinium to tackle thermal stress. Considering the potential applications of this knowledge to confront the threat of coral bleaching prevalence, more study especially in terms of cellular and molecular responses by omics approaches is needed to enhance the understanding of coral-Symbiodinium tolerance toward climate change, particularly heat stress.